A simple assay for glutathione in whole blood1. Issue 10 (21st May 2015) - Hakuna, Lovemore; Doughan, Brandon; Escobedo, Jorge O.; Strongin, Robert M.
<x xml:space="preserve">Abstract</x> A simple dried blood spot isolation protocol yields glutathione samples that are free from optical interferents. Fluorescence detection and quantitation is achieved using a fast response probe selective for glutathione.